1994
DOI: 10.1177/109019819402100109
|View full text |Cite
|
Sign up to set email alerts
|

Research in Dental Health Education and Health Promotion: A Review of the Literature

Abstract: This article presents a review of research in dental health education and health promotion. In the period 1982 to 1992, a total of 57 studies evaluating the effectiveness of interventions to alter individuals' behavior related to dental health were identified. Combining the results of these 57 studies with descriptive articles published over the same period, it appears that dental health education can result in improvements in objective measures of dental health behaviors and actual oral health measures, but h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 80 publications
6
88
2
3
Order By: Relevance
“…Oral Hyg. (Brown, 1994;Locker, 1996, 1998;Watt, 2005).The aforemention evidence implies that people have an inclination for easy ways to improve their oral health status. Modern lifestyle mandates short break times and quick meals for most of those who have outdoor occupations.…”
Section: Discussionmentioning
confidence: 99%
“…Oral Hyg. (Brown, 1994;Locker, 1996, 1998;Watt, 2005).The aforemention evidence implies that people have an inclination for easy ways to improve their oral health status. Modern lifestyle mandates short break times and quick meals for most of those who have outdoor occupations.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] This does not mean that there is no point in dentists providing dietary advice. Instead it highlights the need for better quality research into this area.…”
Section: Evidence On Dietary Interventions In Primary Carementioning
confidence: 99%
“…[1][2][3][4][5] However better quality evidence from randomised controlled trials with other primary health care professionals have highlighted the impact of dietary advice on changing dietary patterns. 6 Evidence-based guidelines now outline ways of helping patients improve their diets.…”
Section: N B R I E Fmentioning
confidence: 99%
“…Knowledge about susceptibility to periodontal disease, dry mouth and prevention of oral and dental problems as well as effective management of these conditions is very important for people with diabetes (27). Studies have shown that improved knowledge about oral health and dental prerequisite for self-care behaviors (18,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about susceptibility to periodontal disease, dry mouth and prevention of oral and dental problems as well as effective management of these conditions is very important for people with diabetes (27). Studies have shown that improved knowledge about oral health and dental prerequisite for self-care behaviors (18,27,28). Insufficient knowledge of oral health (Such as ignoring warning signs and symptoms of oral disease) may increase the risks associated with oral health or cause the patient's diabetes self-care behavior very oral health teeth do not matter (29,30).…”
Section: Introductionmentioning
confidence: 99%